Implications of productivity growth in Pakistan: An economy-wide analysis - Debowicz, Darío; Dorosh, Paul A.; Robinson, Sherman; Haider, Syed Hamza (International Food Policy Research Institute, 2012)
Public investments and policies under Pakistan’s new Framework for Economic Growth are expected to lead to substantial gains in productivity, especially in the industrial and service sectors of Pakistan’s economy. Computable General Equilibrium (CGE) model simulations using a new 2008 Social Accounting Matrix (SAM) for Pakistan show that achieving high productivity growth targets broadly consistent with the Framework for Economic Growth would imply a 9.3 percent per year gain in average household income (compared to trend growth in household incomes of 5.8 percent). Accelerating agricultural growth as well, however, would result in even greater overall economic growth with an additional 2.6 percent gain in average household income. Moreover, with accelerated agriculture growth, real incomes of poor household groups rise substantially, by an additional 2.9 to 4.5 percent, as food-deficit urban poor and poor rural non-farm households benefit from lower real food prices, and agricultural growth spurs rural non-farm output and incomes.